Diretrizes pedagógicas do Programa Segundo Tempo e suas relações com as ações cotidianas dos núcleos - Teixeira, Fabiane Castilho (2012)
The aim of this study was to analyze how core coordinators and monitors involved with the Program Segundo Tempo act and apply the actions and planning methodology proposed by this Program before the coaching and counseling job of the collaborator team 14. In order to identify the participants of the study, carried out a survey with the Ministry of Sports, with Covenant of which would be under the responsibility of the EC 14. The Convened - the city hall of a municipality of State of São Paulo, composed by 10 educational sports centers- it was this research focus. As a support to the analysis done, there is a theoretic system of references focused on professional formation in Physical Education, the guidelines of the PST and the administrative structure and managerial worked by the National Secretary of Sport Education. To achieve the objective, the method chosen was a descriptive and qualitative research, developing itself from analyzes, guidelines and reflections of the researcher, member of the collaborator team 14, with the social actors surveyed. The participants were a general coordinator, an educational coordinator, 10 coordinators core, 10 sports monitors, five complementary activities monitors and 120 beneficiaries by the program Segundo Tempo. Data collection occurred through semi-structured interviews, field diary and with the use of questionnaires. The results indicated that due to the collective work of counseling and monitoring, the actions of the EC 14 professionals surveyed, there was a maturation of the proposals from Covenant. The interventions were based on discussions about the purposes of the PST and guidance on how to face problems found in the nuclei. It became clear that the Covenant has advanced in managerial and pedagogical points, which is important for its proper functioning; professionals have demonstrated a better understanding and commitment to their actions, effectively assuming the planning and their development in the daily core; advances occurred in most methodological procedures, it is highlighting the more effective participation of beneficiaries in the classroom. We conclude that the work of the collaborator team 14 was placed as essential to the improvement of the actions of the social actors involved and effectiveness of continuing education triggered by Sneed/ME hence to the quality and care to beneficiaries. It is hoped that this research will contribute to the reflections on the process of training in Physical Education as well as the pedagogical practice of teachers in the area and, in particular, with the development of the Segundo Tempo Program of the Ministry of Sports.